Antagonizing the spindle assembly checkpoint silencing enhances paclitaxel and Navitoclax-mediated apoptosis with distinct mechanistic - Ana C. Henriques (Nature Portfolio, 2021)
Abstract Antimitotic drugs arrest cells in mitosis through chronic activation of the spindle assembly checkpoint (SAC), leading to cell death. However, drug-treated cancer cells can escape death by undergoing mitotic slippage, due to premature mitotic exit. Therefore, overcoming slippage issue is a promising chemotherapeutic strategy to improve the effectiveness of antimitotics. Here, we antagonized SAC silencing by knocking down the MAD2-binding protein p31comet, to delay mitotic slippage, and tracked cancer cells treated with the antimitotic drug paclitaxel, over 3 days live-cell time-lapse analysis. We found that in the absence of p31comet, the duration of mitotic block was increased in cells challenged with nanomolar concentrations of paclitaxel, leading to an additive effects in terms of cell death which was predominantly anticipated during the first mitosis. As accumulation of an apoptotic signal was suggested to prevent mitotic slippage, when we challenged p31comet-depleted mitotic-arrested cells with the apoptosis potentiator Navitoclax (previously called ABT-263), cell fate was shifted to accelerated post-mitotic death. We conclude that inhibition of SAC silencing is critical for enhancing the lethality of antimitotic drugs as well as that of therapeutic apoptosis-inducing small molecules, with distinct mechanisms. The study highlights the potential of p31comet as a target for antimitotic therapies.